Sex Recession Phenomenon from the Perspective Maqashid Sharia Based on Objectives Marriage Law in Indonesia - Pelu, Ibnu Elmi Acmad Slamat; Asfia, Hilyatul; Tarantang, Jefry; Supriadi, Akhmad (Institut Agama Islam Negeri Curup, 2022)
The sex recession is an implementation of worries about household responsibilities. Marriage, which is supposed to be a requirement for the legality of sexual relations, has experienced a shift. Marriage is no longer considered an appropriate institution with a modern lifestyle in several not Muslim-majority countries. The objective of this research is to offer solutions to the problem of a sexual recession that some of the world's most developed countries are currently facing. This type of research is empirical-normative research. The data were sourced from official news reports and reputable journals that revealed the sex recession in developed countries, such as the United States, England, Australia, and Asian countries such as Japan, South Korea, Singapore, and China. The research was conducted using a phenomenological approach, a conceptual approach, and a philosophical approach. The results of this research show that the epistemology of marriage in Islamic law is a solution to overcome the sex recession during the Covid-19 pandemic. In an ideal world, the phenomena of sex recession may be handled by adopting Islamic law's epistemology in terms of marriage. Even Indonesian marriage law can dispel sex recession by building awareness and understanding of the nature of marriage (maqasid marriage), which is systemically capable of maintaining offspring, self-respect, and religion.